Price theory and applications - Landsburg, Steven E. (Thomson Learrning, 2005)
Landsburg (University of Rochester) studies the ways in which individuals and firms make choices, and the ways in which these choices interact with each other. He focuses on positive questions as to what is or will be, as opposed to normative speculation about what ought to be. The intermediate textbook examines both the market for goods which are supplied by firms and purchased by individuals, and the market for inputs to the production process (such as labor) that are supplied by individuals and purchased by firms. The sixth edition incorporates more current examples from the new economy.